Validasi Enzyme Linked Immunosorbent Assay Untuk Deteksi Antibodi Terhadap Trypanosoma evansi (VALIDATION OF AN ENZYME LINKED IMMUNOSORBENT ASSAY FOR DETECTION OF ANTIBODY ANTI-TRYPANOSOMA EVANSI) - Subekti, Didik Tulus; Yuniarto, Ichwan (Jurnal Veteriner, 2020)
Surra is a disease caused by Trypanosoma evansi (T.evansi) infection. Indonesia was known as an endemic country for Surra.  Development of Enzyme Linked Immunosorbent Assay (ELISA) is very useful for early detection of Surra and for routine surveillance of animals infected by T.evansi. In Indonesia the development of ELISA kit for the detection of antibodies to T.evansi was reported in 1999 and 2003. Unfortunately, the assay performance was still unsatisfactory because it had a low sensitivity (81-89%). Therefore, the development of the validated ELISA kit which is applied nationally in Indonesia is very important. Validation was performed to evaluate the performance of ELISA kit, especially their diagnostic sensitivity, specificity and accuracy. Validation was also carried out to evaluate the method and criteria for determining definitive and universal cut-off values. The results of the validation showed a high sensitivity and specificity that are 95.8% and 98.2% using receiver operating curve (ROC) analysis. Diagnostic accuracy, sensitivity and specificity for advanced validation using universal cut-off values are 96.15%; 93.75% and 98.21% respectively. The best criteria for determining the universal cut-off value is MSD ? 2SD, S / P?  40, SNP ?  25. The cut-off value that can be applied to produce better assay performance based on evaluation by two different operators is MSD ?  2SD.